An ancient family of lytic polysaccharide monooxygenases with roles in arthropod development and biomass digestion - Federico Sabbadin (Nature Portfolio, 2018)
LPMOs catalyze the oxidative breakdown of polysaccharides, thereby facilitating biomass degradation. By analyzing the digestive proteome of firebrats, the authors here identify a yet uncharacterized LPMO family and provide phylogenetic, structural and biochemical insights into its origin and functions.